Structural characterisation of textured gold nanowires. (5th March 2012) - Maurer, Florian; Brotz, Joachim; Miehe, Gerhard; Karim, Shafqat; Fuess, Hartmut
Gold nanowire ensembles of high aspect ratio were grown by electrodeposition into nanoporous polymeric templates. Under dc electrodeposition conditions a strong <110> texture of the nanowires was observed, whereas under ac deposition conditions a preferred growth direction in <100> was found. Transmission electron microscopy (TEM) and X–ray diffraction (XRD) investigations confirm the broken bond model describing the different textures of nanowires. The dc electrodeposition leads to large oriented grains, resulting in a strong <110> texture over the whole nanowire while ac electrodeposition leads to small grains of random orientation at the beginning of the growing process. The <100> texture starts to develop at higher aspect ratios which are confirmed by TEM and X–ray line profile analysis.